Neuro-inflammation and Serum Cytokine Levels in Schizophrenia Patients - Ahmed Abbas Barh Aljamah; Majid Komijani (Academia Open, 2025)
General Background: Schizophrenia (SCZ) is a chronic and multifactorial neuropsychiatric disorder characterized by disturbances in cognition, emotion, and behavior, affecting approximately one percent of the global population. Specific Background: Recent studies have increasingly implicated neuroinflammation and immune system dysregulation, particularly involving cytokines, in the pathophysiology of SCZ. However, the specific roles and interactions of inflammatory mediators such as interleukin-8 (IL-8), interleukin-10 (IL-10), and tumor necrosis factor-alpha (TNF-α) remain unclear. Knowledge Gap: Limited empirical data exist on how these cytokines correlate with clinical characteristics and demographic factors in SCZ, especially regarding gender differences and their potential as biomarkers. Aims: This study aimed to assess serum levels of IL-8, IL-10, and TNF-α in SCZ patients compared to healthy controls using ELISA and to analyze their interrelationships. Results: Findings revealed significantly higher serum concentrations of IL-8, IL-10, and TNF-α in SCZ patients (p<0.0001), with IL-8 levels notably elevated in female patients. Novelty: This research highlights IL-8 as a gender-sensitive biomarker of neuroinflammation in SCZ, contributing to the understanding of immune involvement in its pathogenesis. Implications: The results suggest that cytokine profiling may aid in identifying inflammatory subtypes of SCZ and support the development of targeted immunomodulatory therapies.Highlight : The study confirms elevated IL-8, IL-10, and TNF-α levels in SCZ patients compared to controls. Results suggest that SCZ involves neuro-inflammatory processes linked to immune system activation. Cytokines may serve as useful biomarkers for developing targeted therapeutic strategies in SCZ. Keywords : Schizophrenia (SCZ), Neuroinflammation, IL-8, IL-10, Tumor Necrosis Factor-alpha (TNF-α)